Doctors have a limited role in managing obesity - Moyez Jiwa; Catherine Krejany; Epi Kanjo (The Journal of Health Design, 2021)
It's hard for physicians to discuss weight issues with patients. While the problems of overweight and obesity continue to grow, physicians feel increased pressure to curb the trend. Significant innovation is needed to deliver strategies that help patients manage their weight.